2021
DOI: 10.3389/fcimb.2021.684704
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of a Novel Virulent Klebsiella Phage Kp_Pokalde_002 in a Mouse Model

Abstract: Phage therapy is one of the most promising alternatives to antibiotics as we face global antibiotic resistance crisis. However, the pharmacokinetics (PK) and pharmacodynamics (PD) of phage therapy are largely unknown. In the present study, we aimed to evaluate the PK/PD of a locally isolated virulent novel øKp_Pokalde_002 (Podoviridae, C1 morphotype) that infects carbapenem-resistant Klebsiella pneumoniae (Kp56) using oral and intraperitoneal (IP) route in a mouse model. The result showed that the øKp_Pokalde_… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…To more clearly show that LPKP is inhibited and lysed by endolysin in mice, we counted the bacterial load in the lungs of mice. The assay results showed that LysCA and LysG24 can effectively inhibit the growth of the host bacteria LPKP in vivo and relieve inflammation in the lung tissue, similar to the results of several previous in vivo studies of endolysin therapy ( Peng et al, 2019 ; Dhungana et al, 2021 ). As expected, based on both the clinical signs and the bacterial load in the lungs of mice, LysCA showed a better therapeutic effect.…”
Section: Discussionsupporting
confidence: 86%
“…To more clearly show that LPKP is inhibited and lysed by endolysin in mice, we counted the bacterial load in the lungs of mice. The assay results showed that LysCA and LysG24 can effectively inhibit the growth of the host bacteria LPKP in vivo and relieve inflammation in the lung tissue, similar to the results of several previous in vivo studies of endolysin therapy ( Peng et al, 2019 ; Dhungana et al, 2021 ). As expected, based on both the clinical signs and the bacterial load in the lungs of mice, LysCA showed a better therapeutic effect.…”
Section: Discussionsupporting
confidence: 86%
“…Many studies have reported that phage preparation does not cause changes in inflammatory factors in animals. For example, phage D29 administered via the endotracheal route did not cause significant changes in leukocytes, neutrophils, lymphocytes, and TNF-α levels in the lungs of healthy mice 24 h after treatment ( Liu et al, 2016 ); phage BcepIL02 administered via IP injection did not cause significant changes in TNF-α levels in the lungs of healthy mice 24 h after treatment ( Carmody et al, 2010 ); and phage Kp_Pokalde_002 administered via IP injection did not cause significant changes in TNF-α and IL-6 levels in the plasma of healthy mice 24 h after treatment ( Dhungana et al, 2021 ). In this study, administration of high-dose phage vB_Kox_ZX8 caused slight changes in TNF-α, IL-6, and IL-10 in the serum, liver, and spleen of mice after 24 h of treatment, but did not induce discomfort in mice.…”
Section: Discussionmentioning
confidence: 99%
“…In other studies of the Podoviridae phage, Klebsiella phage Kp_Pokalde_002 and Pseudomonas phage PEV20 had a longer residence time in mouse blood. The titer of Kp_Pokalde_002 in the blood measured via IP injection of 10 8 PFU reached the maximum at the fourth hour, gradually decreased, and cleared at 48 h ( Dhungana et al, 2021 ). The titer of PEV20 in rat blood measured via intravenous injection of 10 8 PFU reached the maximum within 1 h, gradually decreased, and cleared at 48 h ( Lin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of genomics and phenotyping of phages and their host could improve the efficacy of phage therapy in the future in regard to the choice of phage for the pathogen of interest. In line with the aim of expanding phage research, previously, we reported phages exhibiting lytic activity against multidrug resistant Pseudomonas and Klebsiella [10] and also studied pharmacokinetics and pharmacodynamics of our Klebsiella phage Kp_Pokalde_002 in a mouse model [11]. Here, we report the isolation, genome analysis and taxonomic position of three newly isolated phages targeting MDR human pathogens: Escherichia coli, Klebsiella pneumoniae and Salmonella spp.…”
Section: Introductionmentioning
confidence: 74%